Boosting the performance of energy harvesters subject to white Gaussian vibrations through impedance matching solutions - Song, Kailing; Bonnin, Michele; Traversa, Fabio L.; Bonani, Fabrizio (2022 IEEE International Conference on Environment and Electrical Engineering and 2022 IEEE Industrial and Commercial Power Systems Europe (EEEIC / I&CPS Europe), 2022)
We discuss models of piezoelectric energy harvesters for scavenging energy from random mechanical vibrations, represented by a white Gaussian noise source. We show that circuit theory can be applied to design a matching network, to be interposed between the piezoelectric transducer and the load, able to increase the power transferred to the latter. The second order matching network is compared with a previously proposed solution, based on power factor correction, implemented through a single reactive element. We show that the new architecture boosts the harvested power with respect to the simple, unmatched resistive load, by a factor larger than 9, and with respect to the power factor correction solution by more than 17%.